2021
DOI: 10.1093/ehjci/jeab266
|View full text |Cite|
|
Sign up to set email alerts
|

Left atrial structure and function are associated with cardiovascular outcomes independent of left ventricular measures: a UK Biobank CMR study

Abstract: Aims We evaluated the associations of left atrial (LA) structure and function with prevalent and incident cardiovascular disease (CVD), independent of left ventricular (LV) metrics, in 25 896 UK Biobank participants. Methods and results We estimated the association of cardiovascular magnetic resonance (CMR) metrics [LA maximum volume (LAV), LA ejection fraction (LAEF), LV mass : LV end-diastolic volume ratio (LVM : LVEDV), gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…Raisi-Estabragh et al analyzed LA measurements and cardiovascular risk factors, and cardiovascular disease in individuals from the UK Biobank. Their results showed a significant association of CMR-derived LA volume and function with cardiovascular risk factors, which aligns with our findings [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Raisi-Estabragh et al analyzed LA measurements and cardiovascular risk factors, and cardiovascular disease in individuals from the UK Biobank. Their results showed a significant association of CMR-derived LA volume and function with cardiovascular risk factors, which aligns with our findings [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies examined subjects without known cardiovascular disease or risk factors and determined an average LAtef of 59 ± 5.8% ( n = 120), [ 22 ] and 60% for males and 61% for females ( n = 795) [ 32 ]. Raisi-Estabragh et al examined the volume-based LAtef in a large sample of UK Biobank participants with and without cardiovascular risk factors and disease and found an average LAtef of 61.3% [ 18 ]. In the population-based MESA (Multi-Ethnic Study of Atherosclerosis) study, subjects with and without atrial fibrillation were examined, resulting in an average baseline LAtef of 44 ± 9 % for 322 subjects without atrial fibrillation and 39 ± 10% for 197 subjects with atrial fibrillation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal cohort studies have suggested that persistence or progression of diastolic dysfunction is a risk factor for subsequent heart failure 15 , and our findings suggest that ventricular stiffness is a substrate for the evolution of mixed aetiology heart failure. We also found a unidirectional causal association between left atrial volume and atrial fibrillation, suggesting that it is atrial remodelling that drives this arrhythmic outcome 31 . Lipid profiles are associated with adverse changes in cardiac structure and systolic function, and our findings extend that causal association to diastolic traits 32 .…”
Section: Discussionmentioning
confidence: 57%
“…Indeed, increasing number of studies provide evidence in favour of using many of these metrics as an integral part of the echo report. Impairment of LA reservoir strain is the earliest abnormality that can be detected by echocardiography in the spectrum of atrial cardiomyopathy 3,5–7 . It is easy to measure, reproducible and clearly associated with the risk of major clinical endpoints like cardiovascular hospitalization.…”
Section: Figurementioning
confidence: 99%